A multi-site mixed-method evaluation of ‘Cardiac College for Women’ implementation: perspectives of cardiac rehabilitation patients and providers - Carson, Rachael Pamela; Grace, Sherry L.; Bomtempo, Ana Paula Delgado; Hebert, Andree-Anne; Ross, Marie-Kristelle; Oh, Paul; Ghisi, Gabriela (Frontiers in Cardiovascular Medicine, 2024)
A Cardiac College for Women curriculum was developed to address the dearth of women-focused cardiac rehabilitation (CR) education. This study investigated: (1) patient utilization of the education; (2) acceptability and applicability of the education; as well as (3) patient and CR providers’ experiences implementing it. This was a multi-site, mixed-methods study. After baseline assessments at an academic CR program in two Canadian provinces, the 12 weekly 30-minute structured in-person group education sessions were led by staff in the relevant discipline, with supporting online videos and written materials. Women reported their engagement with the education in weekly diaries, and completed a survey post-program. Semi-structured virtual interviews were held with willing participants and staff delivering the intervention. Transcripts were analyzed concurrently by two researchers independently via NVIVO using text condensation, followed by consensus reconciliation and multi-source validation. Forty patients participated in the women-focused education program, with 28 completing weekly diaries and 36 post-intervention surveys. Participants attended 80% of sessions (67-89%). They spent an average of 30 minutes/week engaging additionally with the online education, with 83% rating the weekly content applicable (73-100%). Overall acceptability was rated 4.3±1.7/5. Twelve patients and 5 staff participated in interviews. Four themes were identified: contextual considerations, staffing and implementation issues, valued aspects, and suggestions for improvement. In conclusion, Cardiac College for Women was established as highly acceptable and applicable to patients, supporting their self-management. The women-specific CR education materials were also established as readily implementable by CR staff.